Universal versus targeted coronavirus disease 2019 (COVID-19) arrival antigen testing on subsequent COVID-19 infections in military trainees - Marquise D. Westbrook; James Aden; John W. Kieffer; Erin L. Winkler; Angela B. Osuna; Theresa M. Casey; Dianne N. Frankel; John L. Kiley; Heather C. Yun; Joseph E. Marcus (Cambridge University Press, 2024)
In this retrospective cohort study of military trainees, symptomatic-only coronavirus disease 2019 (COVID-19) arrival antigen testing decreased isolation requirements without increasing secondary cases compared to universal antigen testing. Symptomatic-only arrival antigen testing is a feasible alternative for individuals entering a congregant setting with a high risk of COVID-19 transmission.